Kedudukan Hukum Cucu dalam Pewarisan menurut Sistem Hukum Islam dan Hukum Perdata di Indonesia - Bhisma Dzaky; Al Qodar Purwo sulistyo (Cattleya Darmaya Fortuna, 2025)
This study discusses the legal position of grandchildren in inheritance according to Islamic and civil law in Indonesia. The research was motivated by differing views on the rights of grandchildren when their parents die before the decedent. The aim is to compare how both legal systems regulate grandchildren’s inheritance rights. The method used is normative juridical research with a comparative approach. The results show that under Islamic law, grandchildren inherit through the substitute heir concept, while in civil law, they inherit through the plaatsvervulling (substitution) mechanism. In conclusion, both systems recognize the rights of grandchildren to inherit, though through different mechanisms.